2021
DOI: 10.3389/fphar.2021.618023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nrf2 in the PM-Induced Vascular Injury Under Real Ambient Particulate Matter Exposure in C57/B6 Mice

Abstract: Short-and long-term exposure to particulate matter (PM) has been associated with cardiovascular disease (CVD). It is well recognized that oxidative stress is a potential major mechanism in PM-induced vascular injuries, in which the nuclear factor E2-related factor 2 (Nrf2) signaling pathway plays a critical role. In the current study, a Nrf2 knockout mouse model was used in combination with an individual ventilated cage (IVC)-based real-ambient PM exposure system to assess the potential vascular injury and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“… 47 Using the angiotensin II‐induced vascular injury model in mice, it has been demonstrated that exposure to particulate matter is associated with vascular wall thickening and that Nrf2 knockout mice exhibited an aggravation of this action, illustrating the important protective role played by Nrf2. 48 Our data show that carnosol restored the levels of both Nrf2 and HO‐1 which were substantially decreased by DEP exposure in the aortic tissue. These results are in complete agreement with the action of carnosol in the re‐establishment of the activity of SOD and concentration of GSH which were depleted by DEP administration.…”
Section: Discussionmentioning
confidence: 55%
“… 47 Using the angiotensin II‐induced vascular injury model in mice, it has been demonstrated that exposure to particulate matter is associated with vascular wall thickening and that Nrf2 knockout mice exhibited an aggravation of this action, illustrating the important protective role played by Nrf2. 48 Our data show that carnosol restored the levels of both Nrf2 and HO‐1 which were substantially decreased by DEP exposure in the aortic tissue. These results are in complete agreement with the action of carnosol in the re‐establishment of the activity of SOD and concentration of GSH which were depleted by DEP administration.…”
Section: Discussionmentioning
confidence: 55%
“…8 In this study, we found that curzerene can significantly inhibit the expression of GSTA4 in the glioma cell types U251 and U87. GSTA4 is an important biphasic detoxification enzyme in human body, which is involved in the combination of GSH with reactive oxygen species, [22][23][24][25][26][27][28][29] Recently, GSTA4 has also been shown to affect the progression of colon cancer, as well, and this effect involves the proapoptotic metabolite 4-HNE. Specifically, in colon cancer, activator protein 1 regulates the production of 4-HNE by affecting the c-Jun/Nrf2 complex, which then results in an increase in the level of GSTA4 in cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that curzerene can significantly inhibit the expression of GSTA4 in the glioma cell types U251 and U87. GSTA4 is an important biphasic detoxification enzyme in human body, which is involved in the combination of GSH with reactive oxygen species, cell metabolites, chemotherapy drugs, and other potentially damaging molecules 22–29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs regulate the expression of ROS-related genes and the dependent signaling pathways Since there is evidence that CYP1A1 and transcription factor Nrf2 are protective against PAHs and ambient PM-induced pro-oxidative damage in various cell types [31,32], we investigated their alterations in PAH-treated VSMCs. The mRNA levels of CYP1A1 were dramatically increased in BaA-and BAQ-treated VSMCs in a time-dependent manner, and these alterations were only partially, but signi cantly, inhibited by NAC treatment (Fig.…”
Section: Pahs Regulates Matrix Metalloproteinase Expression and Activity Through Ros Generationmentioning
confidence: 99%